Swift monitoring observations of Mrk 231: detection of ultraviolet variability. Issue 4 (18th August 2018) - Yang, Lilan; Dai, Xinyu; Lu, Youjun; Zhu, Zong-Hong; Shankar, Francesco
ABSTRACT: We analyse 168 Swift monitoring observations of the nearest broad absorption line quasar Mrk 231 in the ultraviolet (UV) and X-ray bands, where we detect significant variability in the UV (∼2246 Å) light curve with a null probability of 4.3 × 10 −10 for a constant model. Separately, from an archival sample of Swift observed active galactic nuclei (AGNs), we measure the relation between UV excess variance and luminosity, finding that the normalized UV excess variance decreases with luminosity. Comparing to this mean relation, the normalized UV excess variance of Mrk 231 is smaller, however within the scatter characterizing the full population. The upper limit of the X-ray excess variance is consistent with other AGN. The power spectrum density (PSD) of the UV light curve can be well fit by a power-law model with a slope of 1.82 ± 0.14 between 10 −7.5 and 10 −6 Hz, consistent with those for typical AGN, with no obvious quasi-periodical oscillation peaks. The UV variability and its power spectrum suggest that a significant amount of the UV emission of Mrk 231 is from the accretion disc. The consistencies in the normalized UV variability and the shape of the PSD between Mrk 231 and other normal AGN suggest that the origin of UV variability of broad absorption line quasars is similar to other AGN, and dust scattering at large scales such as the torus is not a dominating process for the UV emission of Mrk 231. Significant scattering, if present, is constrained to smaller than ∼10 light days. We perform lagged correlation analysis between the UV and X-ray light curves and find the correlation insignificant within the present data.